2015
DOI: 10.1111/tid.12423
|View full text |Cite
|
Sign up to set email alerts
|

Decreased secretion of Paneth cell α‐defensins in graft‐versus‐host disease

Abstract: Background: Intestinal microbial ecology is actively regulated by Paneth cell-derived

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 21 publications
1
55
0
Order By: Relevance
“…Antibiotic treatment has been shown to suppress production of Reg3α in Paneth cells, which prevents colonization by pathogens; 22, 23 similarly, metabolites of commensal Clostridiales mediate colonization resistance and maintain a microbiota supporting integrity of the intestinal epithelial barrier. Furthermore, commensal Clostridiales have been identified as important producers of short chain fatty acids (SCFAs) such as butyrate, which maintain intestinal regulatory T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic treatment has been shown to suppress production of Reg3α in Paneth cells, which prevents colonization by pathogens; 22, 23 similarly, metabolites of commensal Clostridiales mediate colonization resistance and maintain a microbiota supporting integrity of the intestinal epithelial barrier. Furthermore, commensal Clostridiales have been identified as important producers of short chain fatty acids (SCFAs) such as butyrate, which maintain intestinal regulatory T cells.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report [12] demonstrated that GI-GVHD predisposed to enteric bacterial BSIs; the incidence of enteric bacterial BSI was almost 3 times greater after GI-GVHD development than before in the first 120Àdays after allo-HSCT. In a mouse model, loss of Paneth cells led to reduced secretion of a-defensins, antimicrobial peptides required for maintaining intestinal microbial ecology, resulting in a profound loss of diversity and an expansion of gramnegative bacteria in the intestinal microbiome [26][27][28][29]. Alterations in the intestinal microbiome have also been observed in allo-HSCT recipients with GI-GVHD [30].…”
Section: Discussionmentioning
confidence: 99%
“…Changes to patients' gastrointestinal tracts during HCT may in turn affect the gut microbiota. For example, overgrowth of pathobionts may result from a loss of antimicrobial peptide-producing Paneth cells in the small intestine (71)(72)(73). Indeed, loss of Paneth cells is a marker of GvHD risk in humans (74).…”
Section: Il-22mentioning
confidence: 99%